Comparison of Simulated and Observed Current Velocities in Karimata and Gaspar Straits - Mukti Trenggono; Bayu Priyono; Rizqi Rizaldi Hidayat; Teguh Agustiadi (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
Karimata and Gaspar Straits were the connector between the South China Sea and Indonesian Seas, which played a role in transporting the Indonesian Through Flow. The current velocities in both straits were studied by comparing outputs from the INDO12 physical ocean model simulation against observation results from the South China Sea-Indonesian Seas Transport Exchange (SITE) program. In general, the magnitudes of the zonal and meridional model current velocities are weaker than observations. Notably, the B1 and B4 moorings show uncertain model values most of the time. It is understandable considering that B1 and B4 moorings are located in a narrow strait (Gaspar Strait), near the coasts. On the contrary, B2 and B3 moorings show comparable magnitude to the two zonal and meridional components' observations Keywords: Karimata Strait, Current Velocities, INDO12, SITE Program